Factors Affecting Risk of Musculoskeletal Disorders (MSDs) Complaints in Spring Production Workers - Nisrina Tiara Sani; Noeroel Widajati (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction : Musculoskeletal Disorders (MSDs) are one of the occupational diseases with complaints thatfelt in the skeletal muscle. Musculoskeletal complaints can occur in any sector of work. one of the sector isin informal sector workers. The aim of this research was to analyze the relation between individual factorswith occupational factors on musculoskeletal complaints in spring production workers.Methods : This research was an observational research with cross sectional approach. The sample in thisresearch was 23 respondents in the production unit. Sampling in this research was conducted by totalpopulation. Data of respondent characteristics musculoskeletal complaints were obtained through interviewsconducted to respondents by filling out standardized questionnaires. Work posture data were analyzed usingRapid Entire Body Assessment (REBA) and musculoskeletal complaints data were analyzed using theNordic Body Map (NBM) method. Statistical tests were analyzed using the Contingency Coefficient test.Results : The results of the research to 23 respondents showed that the majority of respondents as manyas 15 respondents (65.21%) had MSDs complaints in the high pain severity category. Risk factors relatedto Musculoskeletal Disorders complaints were age. smoking habit. sex. nutritional status. works duration.work posture and physical workload. The data obtained were analyzed using the Contingency Coefficienttest.Conclusion : Factors causing Musculoskeletal Disorders that had the strongest relationship were odd ornon-ergonomic work posture of workers (r = 0.632) with positive relation direction. meaning that the higherthe risk of work posture. the higher the risk for experiencing MSDs complaints.